Pembuatan Iklan Game Berbasis Instagram - Agnes Renica Irwan; Riwinoto Riwinoto (Politeknik Negeri Batam, 2021)
Current developments have made online media or social media a platform that is widely used and in demand, and there have been many uses of social media such as Instagram for advertising or promotion. To promote products, among others, game ads